Avaliação da acessibilidade e do atendimento espacial das escolas públicas em área urbana: estudo de caso na cidade de Fortaleza - Rodrigues, Sueli Nogueira (2010)
The expansion of public education implemented by the educational policies, since the 90s, coupled with the uncontrolled growth of cities, has generated an increase of the distances of the residents to the public schools. These two factors lead to the need to evaluate the spatial accessibility and the attendance of the public schools in the cities, because the distance to be travelled in the home-school path is a decisive factor for keep the student in school, especially for the 7 to 14 years old children. Therefore, this study is to evaluate the educational policies of attendance and of spatial accessibility of public school in a region of Fortaleza/CE. This evaluation has as main element the mandatory provision of basic public education for all 7 to 14 years old children (LDB 9695/96). Thus, from the design of a methodology of analysis of the spatial distribution of the public schools, it was used the Geographic Information System (SIG), as computational tool for analyze the educational units in the city region bounded by the administrative boundaries of Regional Executive Secretary V (SER V). After the analysis, it was found that the basic public education does not meet all the census sectors in the most of neighborhoods that comprise the area in study, as well as the four neighborhoods that meet the accessibility by the shift criteria in study do not proffer sufficient vacancies. And, by adding the schools that belong to the city with the ones that are state property, it is noted that remains the lake of attention to the offered enrollments and primarily to the accessibility issues. These factors converge to identify a spatial distribution without adequate planning to the real needs to the local related to the basic public education, as well as the non-compliance of the current educational policies in the country. It is considered that this type of evaluation should be very useful in the elaboration of educational public policies, mainly related to the definition of the localization on the accessible schools in urban areas, aiming more detailed knowledge about the reality in the search for effective solutions.